Empowering housewives through green marketing: Fostering eco-friendly household products for sustainable consumption - Sriayudha, Yayuk; Octavia, Ade; Simatupang, Johannes; Lubis, Tona Aurora (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
The escalating concern over the green gap phenomenon, which underscores a discord between consumers' environmental concerns and purchasing behaviours, has accentuated the importance of exploring eco-friendly consumption patterns. This study delves into the multifaceted factors influencing the purchasing behaviour of eco-friendly household products, focusing on the dynamic interplay among consumer knowledge, values, subjective norms, and perceived behavioural control. Specifically, it aims to elucidate how these variables collectively inform housewives' attitudes towards eco-friendly products and purchasing behaviours. The research gathered data from 300 respondents across Jambi City and Sungai Penuh City within Jambi Province, employing principal component analysis and structural equation modelling to scrutinize the hypothesized relationships between the constructs. The findings underscore consumer values, subjective norms, and perceived behavioural control significantly and positively influence consumer attitudes towards eco-friendly household products. Moreover, a pronounced positive correlation between consumer attitudes and eco-friendly purchasing behaviour was identified, whereas the impact of consumer knowledge on consumer attitudes emerged as negligible. This research enriches the theoretical discourse on eco-friendly purchasing behaviour, particularly concerning household products. It offers critical insights for marketers, policymakers, and environmental advocates aiming to foster sustainable consumption practices by pinpointing the pivotal factors that shape consumer attitudes and behaviours. Additionally, the study lays a robust groundwork for subsequent research endeavours to bridge the green gap and advance environmental sustainability through enlightened consumer decisions.